(untitled) (International Journal of Physiotherapy, 2018)
Background: Dynamic balance is an ability to move two or more body parts under control. The split and squat jump exercise primarily strengthen gluteus, hamstring muscles, quadriceps, and calves muscles, as well as provide cardiovascular benefits. The objectives of the study were to find the effect of split jump and squat jump exercise on dynamic balance and to compare the effect of exercise on the dynamic balance among female netball players in KPJ University College. Methods: An experimental design with total 80 female subjects were selected and divided equally to 40 subjects in each group. The Star Excursion Balance Test was used to measure the outcome of dynamic balance before and after the intervention. Group A received split jump exercise whereas Group B received squat jump exercise. The intervention was given for six weeks with three sessions for each week. After six weeks of intervention, the researcher checked dynamic balance for both groups. Results: The result showed that there is a significant difference between the groups with P-values 0.0043, 0.0001, 0.0471,0.0001 for anterior, lateral, posterior and medial respectively. Conclusion: The study concluded that both exercises could improve dynamic balance. However, the squat jump exercise is more effective to improve dynamic balance among netball players.